Structural and Synaptic Organization of the Adult Reeler Mouse Somatosensory Neocortex: A Comparative Fine-Scale Electron Microscopic Study of Reeler With Wild Type Mice - Prume, Miriam; Rollenhagen, Astrid; Lübke, Joachim H. R. (Frontiers in Neuroanatomy, 2018)
The reeler mouse has been widely used to study various aspects of cortico- and synaptogenesis, but also as a model for several neurological and neurodegenerative disorders. In contrast to development, comparably little is known about the neuronal composition and synaptic organization of the adult reeler mouse neocortex, which was investigated here at the fine-scale electron microscopic level. In the the ‘barrel field’ of the adult reeler mouse somatosensory neocortex neocortex, , the characteristic six-layered structure is no longer existent but replaced by a conglumarate of neurons organized in homologous clusters with maintained morphological identity and heterologous clusters between neurons and/or oligodendrocytes. These clusters are loosely scattered throughout the neocortical mass, but were also infrequently found in the white matter. Layer 1, if existent, seems to be diluted into the volume of the neocortex with no clear boundary to the underlying neocortical mass. Layer 1 also contains clusters of migrated or persistent neurons, oligodendro- and astrocytes. In addition, myelinated and unmyelinated axons, often organized in massive fiber bundles, are found throughout the neocortex and white matter. A prominent and massive thalamocortical projection traverses through the neocortex, always accompanied by numerous ‘active’ oligodendrocytes. In the adult reeler mouse neocortex, synaptic boutons terminate on somata, dendritic shafts, spines of different types and axon initial segments with no signs of structural distortion and/or degeneration, indicating a ‘normal’ postsynaptic innervation pattern of neurons. In addition, synaptic complexes between boutons and their postsynaptic targets are tightly ensheathed by fine astrocytic processes. In conclusion, the neuronal clusters may represent a possible alternative organization principle in adult reeler mice ‘replacing’ layer formation. If so, these homologous clusters may represent individual ‘functional units’ where neurons are highly interconnected and may function as the equivalent of neurons integrated in a cortical layer. The structural composition and postsynaptic innervation pattern of neurons by synaptic boutons may provide the structural basis for the establishment of a functional although altered cortical network in the adult reeler mouse.